A study to assess awareness on eye donation and willingness to pledge eyes for donation in adult population in Gwalior district (M.P.), India - Tiwari, Ranjana; Diwakar, Avadhesh; Marskole, Priyesh; Bhargo, Leena; Anwar, Danish (International Journal of Research in Medical Sciences, 2017)
Background: Purpose of current study was to determine the awareness of eye donation and willingness to pledge eyes for donation in the government colonies (Central and state govt. colonies) of district Gwalior (M.P.). Corneal diseases constitute a significant cause of visual impairment and blindness in the developing world. Although Strategies to prevent corneal blindness are likely to be more cost effective, visual rehabilitation by Corneal Transplantation remains the major treatment for restoring sight in those who already have corneal blindness. Methods: The present study was undertaken from July 2012 to Dec. 2012 with a total population 2192 was surveyed of people residing in central and state govt. Colonies of district Gwalior in which total of 500 houses were taken. The total population aged 30 years and above were interrogated by a predesigned questionnaire regarding awareness of eye donation, any eye related problem and willingness to pledge eyes for donation. Results: The total respondents were 947 in which 481 (50.79%) were Males and 466 (49.21%) were females. The awareness of eye donation was present in 590 (62.30%) while 357 (37.70%) were not aware. Conclusion: The awareness regarding eye donation should be increased so that the public’s attitude would be more favorable to facilitate an increase in the number of corneas available for transplantation.